HERMENEUTIKA ALQURAN - M. Ilham M. Ilham (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
Normatively, al-Qur’an as Islamic Holy book is trusted to have the absolute truth, but the reading of al-Qur’an as the process of interpretation contains the relative and tentative truth. The process is a response of the interpreter when understanding a text, situation, and social problem. Consequently, there is a gap between al-Qur’an and the interpreter. How could both be close? This article attempts to reveal it through hermeneutic analysis that is developed by Muhammad Shahrour. Based on the analysis, it found that dialectic between revelation (al-Qur’an text), interpreter, and the reality context should be equally functioned. It remembers that al-Qur’an is not a “dead text”. The consciousness about the reality that human problem is ongoing and the context is fluctuatif, but the verses of al-Qur’an is static and its quantity is finite. Hence, it is able to encourage people to make al-Qur’an be a dialogue partner to answer the social problem regarding religion in the present day.